Cover Feature: Expanding the Substrate Scope of Nitrating Cytochrome P450 TxtE by Active Site Engineering of a Reductase Fusion (ChemBioChem 13/2021). (10th June 2021) - Saroay, Rakesh; Roiban, Gheorghe‐Doru; Alkhalaf, Lona M.; Challis, Gregory L.
Abstract : The tryptophan‐nitrating cytochrome P450 TxtE has the potential to be developed into an environmentally benign aromatic nitration biocatalyst. However, the enzyme's narrow substrate tolerance is an impediment to this. The picture shows how randomly mutagenizing a key active site residue led to the discovery of a TxtE variant that efficiently nitrates tryptamine, which is not accepted by the wild‐type enzyme. This demonstrates that directed evolution can be used to create TxtE variants able to nitrate synthetically useful substrates. More information can be found in the Communication by L. M. Alkhalaf, G. L. Challis et al.